2018
DOI: 10.3390/nano8121046
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Mechanism of Interfacial Separation and Slippage of Graphene/Aluminum Nanolaminated Composites

Abstract: Due to their excellent properties and two-dimensional geometry, graphenes (Grs) have been widely used as reinforced fillers in graphene/aluminum nanolaminated composite (GANC). The separation and slippage behavior of the GANC is highly dependent on the interfacial properties between Gr and aluminum (Al). In this study, two interfacial failures of GANCs, i.e., pull-up failure and pull-out failure, were investigated using a molecular dynamics (MD) method. The effects of the crystal orientation of single-crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Similar observations have been made with (8,8) and (10,10) CNTs. Also, the references [7,8], and [11] found a similar trend.…”
Section: Work Done By Pull-out Forcesupporting
confidence: 63%
See 1 more Smart Citation
“…Similar observations have been made with (8,8) and (10,10) CNTs. Also, the references [7,8], and [11] found a similar trend.…”
Section: Work Done By Pull-out Forcesupporting
confidence: 63%
“…Further, it was found that zig-zag CNTs have better pull-out resistance than chiral nanotubes while length and temperature have little effect on the interfacial shear stress. Zhu et al [11] examined the pull-up and pull-out failure of the CNT/graphene interface with MD and revealed that the pull-up resistance aroused from the forces of interfacial atoms, whereas the pull-out resistance was produced due to atomic forces of the atoms at the crack tip. Also, it was found that the crystal orientation of Al and the environmental temperature were the sensitive factors for interfacial strength.…”
Section: Introductionmentioning
confidence: 99%
“…Since graphene also has much greater current density and thermal conductivity values than copper, copper overcomes this issue and provides the characteristics and opportunities to deliver the required thermal management by incorporating graphene. On the other hand, the orientation of graphene in composites significantly alters the thermal properties of graphenemetal materials, bringing different enhancements in nanocomposites [16][17][18][19][20][21]. Further studies are required to investigate the contribution of graphene to the thermal conductivity of graphene-copper nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a two-dimensional (2D) sheet consisting of covalently bonded sp 2hybridised carbon atoms with exceptional electrical, mechanical and thermal properties [15][16][17][18]. Graphene is considered an attractive reinforcement to enhance the mechanical properties (such as hardness and strength) of MMCs, including Gr-Cu [19][20][21][22][23][24][25], Gr-Cu-W [26], Gr-Fe [27], and Gr-Al [28][29][30]. Recent studies have shown that graphene can improve the arc erosion resistance of MMCs.…”
Section: Introductionmentioning
confidence: 99%